2003
DOI: 10.1152/ajpheart.00651.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n-3 PUFAs affect the blood pressure rise and cardiac impairments in a hyperinsulinemia rat model in vivo

Abstract: The cardiovascular consequences of eicosapentaenoic acid (EPA)- and docosahexaenoic acid (DHA)-specific intake were evaluated in vivo in a hyperinsulinemia (HI) model induced by dietary fructose intake. Wistar rats were fed a diet containing (or not for control) either EPA or DHA. The rise in blood pressure (BP), heart rate, and ECG were continuously monitored using an intra-abdominal telemetry system. The myocardial phospholipid fatty acid profile was significantly affected by DHA intake but less by EPA intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 48 publications
9
65
1
Order By: Relevance
“…On the other hand, notwithstanding a significant difference in plasma glucose concentration between the groups, the insulin-tolerance test was not able to demonstrate insulin resistance in the U-HFD rats. In this context, a previous study using an insulin resistance diet model showed that rats that were fed polyunsaturated fatty acid (docosahexaenoic acid) had a short QT interval on the ECG (36). Nevertheless, in our study, no changes were observed in this parameter.…”
Section: Figure 4) Full-length Tachograms (Top) and Rr Power Spectra contrasting
confidence: 77%
“…On the other hand, notwithstanding a significant difference in plasma glucose concentration between the groups, the insulin-tolerance test was not able to demonstrate insulin resistance in the U-HFD rats. In this context, a previous study using an insulin resistance diet model showed that rats that were fed polyunsaturated fatty acid (docosahexaenoic acid) had a short QT interval on the ECG (36). Nevertheless, in our study, no changes were observed in this parameter.…”
Section: Figure 4) Full-length Tachograms (Top) and Rr Power Spectra contrasting
confidence: 77%
“…Animal studies have demonstrated that diets high in saturated fatty acid (SFA) increase BP (2,3), whereas diets enriched with n-3 polyunsaturated fatty acid (PUFA) protect against BP elevation (4)(5)(6). However, epidemiologic evidence regarding the association between various subtypes and individual FA intake, and the risk of developing hypertension remains limited and inconsistent (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…26 Other studies reported a limitation by fish oil of the systolic blood pressure increase in essential hypertension, 27 reno-vascular hypertension 28 and insulin resistance. 29 …”
Section: Experimental Investigations: the Importance Of Aetiologymentioning
confidence: 99%
“…Additionally, this supplement significantly lowered heart rate and reduced the QT interval length. 29 Conversely, a pure EPA supplement also lowered blood pressure but failed to affect heart rate and QT interval. DHA readily enters cardiac membrane phospholipids, but not EPA, suggesting that unlike EPA, the mechanism of action of DHA may involve the regulation of adrenergic function, like b-blockers.…”
Section: Clinical Studiesmentioning
confidence: 99%